Cytogenetic comparison of Cuscuta psorothamnensis and C. veatchii (Convolvulaceae), two species originated from recurrent hybridization between the same diploid parents - Moura Ibiapino, Amalia; Urdampilleta, Juan; García, Miguel A.; Pedrosa-Harand, Andrea; Stefanović, Saša; Costea, Mihai (2024)
Fil: Moura Ibiapino, Amalia. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina.